STEPPING COLORATION OF Co(OH)2/Ni(OH)2 ELECTROCHROMIC FILM PREPARED BY A SIMPLE CHEMICAL BATH DEPOSITION METHOD - M Alvien Ghifari; Desti Riandiani; Juwita Sari; Bambang Ari Wahjoedi (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
Electrochromic smart windows enable dynamic regulation of solar irradiation, thereby contributing to improved energy efficiency in building environments. In this work, Co(OH)₂/Ni(OH)₂ composite films were successfully deposited onto ITO-coated glass substrates via a facile chemical bath deposition method. Two configurations were explored: a homogeneously mixed composite and a double-layer architecture. The structural, morphological, and optical properties of the films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV–Vis spectroscopy. Both film types exhibited voltage-dependent, stepwise color modulation under applied potentials, confirming their electrochromic behavior. Notably, the mixed Co(OH)2/Ni(OH)2 film demonstrated enhanced optical modulation, with a transmittance change (ΔT) of 11.10% and an optical density change (ΔOD) of 0.09 at 0.15 V, increasing to 50.14% and 0.91 at 0.75 V. In contrast, the bilayer configuration showed significantly lower ΔT and ΔOD values of 1.36% and 0.13 at 0.15 V, and 9.64% and 0.31 at 0.75 V. These results highlight the synergistic role of Co(OH)2 in tuning the optical response of Ni(OH)₂-based electrochromic films and suggest that compositional mixing is more effective than stratified layering for optimizing optical contrast in electrochromic devices.